2015
DOI: 10.1177/1937586715603194
|View full text |Cite
|
Sign up to set email alerts
|

Lighting and Nurses at Medical–Surgical Units

Abstract: Thoughtful design of the lighting environment can improve nurses' satisfaction and perception about their working environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…Although Hadi et al (2016) did not demonstrate any influence of age on the overall satisfaction with lighting; the quantity of light; or complaints about glare, shadows, or flickering, the present study found that participants over the age of 55 believed that additional lighting was needed in patient rooms more often than younger participants did. This finding is consistent with published light level guidelines recommending that people over the age of 65 need 2-4 times the amount of light that people of younger ages require (DiLaura et al, 2011).…”
Section: Lighting Considerations Based On Agecontrasting
confidence: 97%
“…Although Hadi et al (2016) did not demonstrate any influence of age on the overall satisfaction with lighting; the quantity of light; or complaints about glare, shadows, or flickering, the present study found that participants over the age of 55 believed that additional lighting was needed in patient rooms more often than younger participants did. This finding is consistent with published light level guidelines recommending that people over the age of 65 need 2-4 times the amount of light that people of younger ages require (DiLaura et al, 2011).…”
Section: Lighting Considerations Based On Agecontrasting
confidence: 97%
“…The practicality of conducting the study in a single room meant that other elements of the physical environment were not consistent with those of a TEC facility, and these elements may influence the overall subjective response as much as or more than lighting. This fact may explain the overall positive nature of the ratings for all conditions, especially given the more negative reactions to lighting systems in TEC facilities reported in several surveys of nurses working directly in these facilities (Hadi et al, 2016;McCunn et al, 2020). Additional research that compares nurse and patient responses to different environment of care settings in real hospitals would better document the responses from the full range of existing environments.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Satisfaction with the workplace may be influenced by the control of the environment. A study investigated the perceptions of the lighting environment and the levels of satisfaction in the workplace, due to variations in lighting among medical-surgical nurses and found a significant relationship between nurse access to lighting controls and satisfaction about the lighting environment [ 101 ]. Demographic variables, specifically age, may also play a role in the effect of lighting conditions on work performance.…”
Section: Resultsmentioning
confidence: 99%